Occurrence, characterization and antimicrobial resistance pattern of pathogenic Salmonella isolated from chicken and chicken meat products - Babar, Ajay; Suryawanshi, Rahul; Deshmukh, Onkar; Kurkure, Nitin; Patil, Vaibhav; Devangare, Ashok; Kulkarni, Ram (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The objective of this investigation was to detect the occurrence, characterization, and antimicrobial resistance patterns of pathogenic Salmonella isolated from samples (400) comprising faecal and cloacal samples, environmental samples, chicken meat, and restaurant meat products collected at Udgir, Maharashtra. Following primary isolation and biochemical tests, two isolates were found to be positive for Salmonella spp. and were subjected to in vitro pathogenicity tests. Salmonella genus identification was accomplished by targeting the genus-specific invA gene, and serotype identification was executed by targeting the spy and sdfI genes with the Polymerase Chain Reaction (PCR) technique. The results showed that both isolates were positive for the S. Typhimurium spy gene, indicating a 0.50% overall prevalence of pathogenic Salmonella Typhimurium. Similarly, Both S. Typhimurium isolates tested positive on virulent marker (invA) based PCR, as well as pathogenic potential on Congo red dye binding assay and haemolysis on 5% sheep blood agar, indicating the efficient use of a targeted gene, invA, for early determination of pathogenic potential of Salmonella isolates. An antibiogram study using 15 antibiotics revealed remarkably high resistance to tetracycline, sulphadiazine, nalidixic acid, and ampicillin, suggesting a spike in multidrug resistance in food-borne pathogens to the most commonly used drugs in animal and human medicine.